Persepsi Mahasiswa Prodi Pendidikan Administrasi Perkantoran Stambuk 23 UNIMED terhadap Implementasi Sila Kemanusiaan dan Persatuan dalam Menghadapi Ujaran Kebencian di Media Sosial Instagram: Penelitian - Andika Rifky Maulana; Erlinda Simbolon; Esa Wulan Br Pasaribu; Kristina Sipayung; Nur Melinda Pradipti Winera; Salmin Wanimbo; Sry Rejeki Lumban Toruan; Yola Febriani Br Purba; Julia Ivanna (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the perceptions of Office Administration Education students at UNIMED regarding the implementation of the Principles of Humanity and Unity in facing hate speech on Instagram. Using a quantitative descriptive approach, data were collected through online questionnaires from 20 students selected via purposive sampling technique. Simple linear regression analysis was used to measure the influence between variables. The results showed a positive and significant relationship between perceptions of Pancasila values and students' ethical responses. This is evidenced by an R Square value of 0.6973, indicating that 69.73% of the variation in students' wise attitudes, such as refraining from provocation and building peaceful narratives, is influenced by their understanding of the values of humanity and unity. The regression equation Y = 2.5986 + 0.9275X confirms that the internalization of Pancasila effectively improves the ability to filter negative content. It is concluded that Pancasila values are proven crucial as a moral foundation and a primary strategy for conflict mitigation in the digital space.